Navajo Girls in Line - Lantz, Paul
This is a pencil drawing of a Navajo Girl.
Paul Lantz donated 41 original illustrations done for children's books (mainly on subjects of Western themes - cows, Indians, Mexican-Americans, etc.) to the Arthur Johnson Memorial Library in October of 1973. He asked that these illustrations never be sold or given away, but that they remain on the property of the library. They all are matted and encased with glass and backings.
Located in Basement Small Box Space 2
Artist is Paul Lantz - Born February 14, 1908 in Stromsburg, Nebraska-Died November 19, 2000 in Santa Fe, New Mexico) spent his early childhood in Montana and Missouri. In Missouri, he studied at the Kansas City Art Institute where he was the youngest student ever enrolled. At the age of seventeen, he traveled to New York for further study at the National Academy and Art Students League. In 1929 Lantz traveled to New Mexico Where until 1939, he worked with artist Randall Davey, Lantz Moved to New Mexico permanently in 1974.
AJML42
Keywords: Lantz, Paul; Navajo People Art; Pencil Art; Drawings; Art; Navajo Children